Overcoming poverty in rural area of Afghanistan through humanising entrepreneurship education programme - Manssoori, Jalatkhan; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
Poverty eradication is one of the vital factors for Afghan youth to be educated, happy and for their wellbeing. Poverty in Afghanistan has increased over time, where most of the people - both men and women, are living in a very high rate of national poverty line. Households in Afghanistan have higher number of young children, relying on child labour, illiterate head and a head employed in informal labour sector. This paper offers validated business model on humanising entrepreneurship programmes to overcome the high rate of national poverty level in Afghanistan. Also, this paper discusses the initial Business Model options - Canvas (BMC) and Value Proposition Design (VPD). This paper adapted the design thinking approach. The approach includes conducting literature review and interviews by utilising BMC and VPC to analyse, formulate and design business model alternatives for Eradicating poverty in Afghanistan. The focus is on how to reduce and eradicate poverty, while creating decent jobs and spur economic growth for youth through humanising entrepreneurship programme. Finally, these youth should be educated, trained and nurtured with relevant knowledge, skills and values in terms of jobs and value creation for themselves and others.